2018
DOI: 10.1101/264580
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Competition in biofilms between cystic fibrosis isolates ofPseudomonas aeruginosais shaped by R-pyocins

Abstract: Pseudomonas aeruginosa is an opportunistic pathogen responsible for a number of different human infections and is the leading cause of morbidity and mortality in cystic fibrosis (CF) patients. P. aeruginosa infections are difficult to treat due to a number of antibiotic resistance mechanisms and the organisms propensity to form multicellular biofilms. Epidemic strains of P. aeruginosa often dominate within the lungs of individual CF patients, but how they achieve this is poorly understood. One of the ways stra… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 26 publications
(36 reference statements)
2
15
0
Order By: Relevance
“…To assess heterogeneity in susceptibility to R-pyocins within these populations, we used partially fractionated R2-pyocin cell lysate from PAO1. To show that other pyocin-associated lytic enzymes such as holin, lysin or other SOSinduced prophage are not responsible for the bactericidal activity against other strains, we included lysates extracted from an isogenic PAO1 R-pyocin mutant lacking the tail fiber gene and chaperone (PAO1ΔR), which produces nonfunctional partial pyocins (58). This strain has an intact lysis cassette, holin genes, and Pf4 prophage.…”
Section: R-pyocin Type Does Not Vary Within a Clonal Cf Population Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess heterogeneity in susceptibility to R-pyocins within these populations, we used partially fractionated R2-pyocin cell lysate from PAO1. To show that other pyocin-associated lytic enzymes such as holin, lysin or other SOSinduced prophage are not responsible for the bactericidal activity against other strains, we included lysates extracted from an isogenic PAO1 R-pyocin mutant lacking the tail fiber gene and chaperone (PAO1ΔR), which produces nonfunctional partial pyocins (58). This strain has an intact lysis cassette, holin genes, and Pf4 prophage.…”
Section: R-pyocin Type Does Not Vary Within a Clonal Cf Population Ofmentioning
confidence: 99%
“…4A). We used Rpyocin containing lysates from the standard laboratory strain PAO1 (an R2-producer) and a PAO1 R-pyocin null mutant lacking a functional R-pyocin (PAO1ΔR), as well as previously described CF isolates A018 (an R2producer), A026 (an R1-producer) and R-pyocin null mutants of each as controls (40,58,59). The spot assay showed that Isolate 1 from Patient 3 was resistant to the R2-pyocins of PAO1 and A018, while Isolates 2 and 3 were susceptible (depicted by the zones of inhibition where the R2-pyocin lysates were spotted) ( Fig.…”
Section: R-pyocin Type Does Not Vary Within a Clonal Cf Population Ofmentioning
confidence: 99%
“…Steve Diggle (Georgia Institute of Technology, Atlanta, GA) described antagonistic interactions between strains of P. aeruginosa occurring through production of R-pyocin bacteriocins also known as tailocins. Directly applied to biofilms, R-pyocins have sufficient antimicrobial activity to cause significant killing of cells within about 4 h. In addition to potential applications, this lethality may account for the observation that certain strains and lineages of P. aeruginosa dominate during CF lung infections (85).…”
mentioning
confidence: 99%
“…Previously, it was reported that the production of two proteases with anti-flagellin activity provides a failsafe mechanism for P. aeruginosa to ensure the maintenance of protease-dependent immunemodulating, they concluded that alkaline protease (AprA) and elastase (LasB) are capable of degrading exogenous flagellin under calcium-replete conditions and prevents flagellin-mediated immune recognition [42]. Finally, during another study authors analyzed strains isolated from cystic fibrosis patients and found mutations as well as genomic arrays which are in accordance with phenotypic variability among populations, this may explain why some epidemic and transmissible P. aeruginosa strains dominate and displace others during infection, authors suggest that pyocyanin production is capable of leading this process and that one possibility is that intraspecies competition is driven by the production of bacteriocins as pyocyanins [43]. All previously described mechanisms may be present in isolated strains in this study since it was found that a high percentage of the strains express biofilm, alkaline protease, pyocyanins and elastase as virulence factors.…”
Section: Discussionmentioning
confidence: 92%